మల్లికా గుచ్ఛము - Madapati Hanumanta Rao (Andhra Saraswata Parishath, 1984)
This book is all about stories
Mallika Guchhamu
Keywords: Telugu; మల్లికా గుచ్ఛము; Mallika Guchhamu; Literature; Telugu; Telugu